Associations Between Community Social Capital and Preservation of Functional Capacity in the Aftermath of a Major Disaster. Issue 11 (14th May 2020) - Gero, Krisztina; Hikichi, Hiroyuki; Aida, Jun; Kondo, Katsunori; Kawachi, Ichiro
Abstract: The strength of social connections in the community ("social capital") is hypothesized to be a crucial ingredient in disaster resilience. We examined whether community-level social capital is correlated with the ability to maintain functional capacity among older residents who experienced the 2011 Great East Japan Earthquake and Tsunami. The baseline of our cohort (mean age, 74 years) was established in 2010, 7 months before the disaster in Iwanuma, a Japanese city located 80 km from the epicenter. Disaster-related personal experiences (e.g., housing damage or relocation) were assessed through a follow-up survey ( n = 3, 594; follow-up rate, 82.1%) conducted in 2013, 2.5 years after the earthquake. Multiple membership multilevel models were used to evaluate the associations between functional capacity, measured by the Instrumental Activities of Daily Living scale, and 3 subscales of community-level social capital: social cohesion, social participation, and reciprocity. Community-level social participation was associated with a lower risk of functional decline after disaster exposure. The average level of social participation in the community also mitigated the adverse impact of housing damage on functional status, suggesting a buffering mechanism.